Hydrophobic nanocoating of cellulose by solventless mechanical milling. Issue 10 (26th April 2016) - Zhao, Mengmeng; Kuga, Shigenori; Wu, Min; Huang, Yong
Abstract : Dry milling of cellulose in a PTFE pot causes friction-transfer of PTFE, leading to nanocoating of cellulose by PTFE. Abstract : The solventless mechanical treatment of native cellulose in a polytetrafluoroethylene (PTFE) vessel was found to cause friction transfer of PTFE to comminuted cellulose particles, resulting in their nanocoating. Cellulose particles after milling were irregular-shaped platelets, with typical sizes of 2–10 μm wide and 0.1–0.4 μm thick (28 h milled). Add-on of PTFE onto cellulose was assessed by weight gain of powder or weight loss of the pot. The PTFE-coated particles were highly hydrophobic and completely repelled from water, with a water contact angle of 110–121°. SEM-EDS analysis showed nearly continuous coverage of cellulose particles by PTFE layers of approx. 10 nm thick, which agreed well with peak-width analysis of X-ray diffraction. This finding may open a new class of solid-phase processing for nanocoating of particles.